Connexin 43 suppression enhances contractile force in human iPSC-derived cardiac tissues - Takada, Takuma; Matsuura, Katsuhisa; Iida, Tatsuro; Koike, Toshiharu; Sekine, Hidekazu; Higashi, Yuhei; Hara, Tsukasa; Sasaki, Daisuke; Fujita, Kyohei; Hinata, Yuto; Yamaguchi, Junichi; Shimizu, Tatsuya (Frontiers in Bioengineering and Biotechnology, 2025)
Connexin 43 (Cx43) plays a crucial role in maintaining synchronous contraction in the heart. However, it remains unclear whether Cx43 directly influences the contractile force and synchrony of entire cardiac tissues. Previously, we successfully developed human-induced pluripotent stem cell (hiPSC)-derived cardiac tissues capable of directly measuring both the contractile force of the entire tissue and cellular synchrony within it. This study aimed to evaluate whether regulating GJA1, the gene encoding Cx43, could enhance contractility and synchrony in these tissues. Using adeno-associated virus (AAV), we mediated GJA1 overexpression (OE) or knockdown (shGJA1) in bioengineered hiPSC-derived cardiac tissues. Under electrical stimulation at 60 ppm, there were no significant differences in contractile force between the AAV-GJA1-OE and control tissues (0.78 ± 0.39 vs. 0.98 ± 0.43 mN, p = 0.32). Synchrony levels were also similar between these groups (p = 0.20). In contrast, shGJA1 tissues demonstrated significantly higher contractile force compared to scramble controls (1.55 ± 0.38 vs. 1.20 ± 0.15 mN, p = 0.039), although the difference in synchrony was not statistically significant (p = 0.08). RNA sequencing data revealed that a total of 37,199 genes were detected, comparing AAV6-GFP control and GJA1-OE treated hiPSC-CMs, as well as AAV6-shRNA scramble and shGJA1 treated hiPSC-CMs. We highlighted several candidate genes potentially contributing to the enhanced contractile force observed in the shGJA1 group. Furthermore, nineteen common genes were identified between the upregulation of shGJA1 compared to scramble and downregulation of GJA1-OE compared to control, which were associated with cell proliferation, transcription, contraction, and BMP signaling pathways. In conclusion, Cx43-OE did not appear to influence contractility and synchrony, meanwhile, Cx43 suppression may effectively improve contractility without impairing the synchrony in the entire cardiac tissues. Cx43 expression beyond a certain threshold may be sufficient to maintain synchronous contraction in the tissues.